"Green", innovative, versatile and efficient carbon materials from polyphenolic plant extracts. (15th October 2020) - Celzard, Alain; Fierro, Vanessa
Abstract: Tannins are polyphenolic molecules of great industrial interest, not only for themselves but also as bio-based precursors for multiple carbonaceous materials with extremely diverse structures, textures and potential applications. In recent years, extensive work has been devoted to these new, predominantly porous carbons, and to their properties. It was therefore time to collect the main results in this invited review, whose objective is to show how a single, inexpensive, non-toxic and commercially available renewable resource can lead to such a wide range of different carbons. Cellular carbons, ordered or disordered mesoporous carbons, carbon gels and vitreous carbons, among others, are presented herein through their textures, morphologies and applications. We show that some of these tannin-derived materials are truly model materials, in the sense of excellent control of their structure. Therefore, they could be successfully used to verify the applicability of certain laws of physics to these carbons, or to observe their limits, for the first time. We end this article with a quick overview of the studies still underway in this area. Graphical abstract: Image 1